2002
DOI: 10.1097/00000542-200209000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Can the Tomographic Aspect Characteristics of Patients Presenting with Acute Respiratory Distress Syndrome Predict Improvement in Oxygenation-related Response to the Prone Position?

Abstract: There are no distinctive morphologic features in the pattern of lung disease measured by computed tomographic scanning performed with the patient in the supine position that can predict response to the prone position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 18 publications
2
22
2
1
Order By: Relevance
“…At the very end, the present lung US findings are consistent with two previous CT studies [9,10]. The change in oxygenation in the prone position did not correlate with either the static distribution of densities in the dorsal lung regions [10] or with lung recruitability in the supine position [9].…”
supporting
confidence: 91%
“…At the very end, the present lung US findings are consistent with two previous CT studies [9,10]. The change in oxygenation in the prone position did not correlate with either the static distribution of densities in the dorsal lung regions [10] or with lung recruitability in the supine position [9].…”
supporting
confidence: 91%
“…At variance with previous studies [20,24,25], our findings were confirmed over the PP session, corresponding to a persistent response. Improving oxygenation by PP is supported by several mechanisms, as previously described [4,26,27].…”
Section: Oxygenation Response To Ppcontrasting
confidence: 63%
“…The predominance of aeration loss in dependent and dorsal lung areas measured by CT scan did not influence the response to PP [20]. Our study confirms that lung morphology does not predict response to PP in terms of oxygenation.…”
Section: Oxygenation Response To Ppsupporting
confidence: 48%
See 1 more Smart Citation
“…Fourth, since the authors used the highest lung score for each of the 12 lung zones they evaluated, even a diffuse pattern may include considerable heterogeneity, as reported in previous studies of lung ultrasound and ARDS (24). Finally, even if lung ultrasound successfully detected changes in aeration, prior studies utilizing CT have shown that aeration changes are not sufficient to identify which patients will have improvements in gas exchange (29).…”
Section: Commentarymentioning
confidence: 98%